EP208/#677 Combination of IGF1R inhibition with PD-1 blockade results in significant anti-tumoral activity in epithelial ovarian cancer. (4th December 2022) - Somri-Gannam, Lina; Sharon, Shilhav Meisel; Hantisteanu, Shay; Mordechai, Hallak; Werner, Haim; Bruchim, Ilan
Abstract : Objectives: The insulin-like growth factor (IGF) system plays a key role in regulating growth and invasiveness in epithelial ovarian cancer (EOC), therefore, is regarded as a promising therapeutic target. Recently, it has been shown that the IGF1 axis can regulate dendritic cells (DC) maturation and T cell activation. Our study aims to investigate the combination effect of IGF1 receptor (IGF1R) inhibition along with anti-PD-1 on EOC. We believe that this combination may reverse immune escape in EOC patients. Methods: EOC cell lines were co-cultured with IGF1R inhibitor (AEW-541)-treated-DCs. DC differentiation and EOC proliferation levels were evaluated by Flow Cytometry Assay (FACS). C57BL/6 mice with established peritoneal ID8 OC were injected with single or combined anti-PD-1 and AEW-541, and their survival was evaluated. Myeloid DCs and T-cell population levels were analyzed by FACS. Finally, RNA from tumors was extracted and submitted for RNAseq analysis (results are pending). Results: IGF1R inhibitor treatment induced DC differentiation. In addition, (AEW-541)-treated-DCs significantly decreased EOC cell proliferation. Combined anti-PD-1/IGF1R treatment decreased tumor weight compared to single treatments. Moreover, the anti-PD-1/IGF1R treatment significantly increased the Myeloid DC1 frequencies by 34% and 40%, and DC2 frequencies by 10% and 24% compared to AEW-541 and anti-PD-1 treatments, respectively. Additionally, the combined treatment increased CD8+ T-cells levels (115%) compared to AEW-541 treatment. Conclusions: IGF1R pathway inhibition in differentiated DCs suppressed EOC cell proliferation. IGF1R inhibitor combined with anti-PD-1 may result in enhanced anti-tumor activity. Thus, restoring the anti-tumor immune response by IGF1R targeting in combination with immunotherapy may be an effective therapy for EOC.